Multifunctional hollow mesoporous degradable carbon nanomaterial as well as preparation method and application thereof

Through hydrothermal synthesis technology, hollow-mesoporous carbon-shell nanomaterials are prepared using monosaccharides and mesoporous silica templates, and their degradability is improved by hydrofluoric acid treatment, which solves the problems of non-degradation and toxicity of existing carbon nanomaterials, and realizes the preparation of multifunctional and biodegradable nanomaterials.

CN119591088APending Publication Date: 2025-03-11NORTHWEST A & F UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466043.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing hollow mesoporous carbon nanomaterials are not degradable, and long-term use leads to accumulation of toxicity. In biomedical applications, it is necessary to treat nitric acid and sulfuric acid to cause additional toxicity, making it difficult to achieve multifunctional integrated biodegradability.

Method used

By designing and preparing methods, using monosaccharides as carbon source and core-shell mesoporous silica as a hard template agent, based on non-enzymatic browning reactions, degradable carbon nanomaterials with hollow-mesoporous carbon shell structure were prepared, and their degradability was improved by hydrofluoric acid treatment.

Benefits of technology

It realizes the preparation of multifunctional hollow mesoporous degradable carbon nanomaterials, with good biocompatibility, low toxicity and degradability, and is suitable for drug delivery, tumor treatment and diagnosis, magnetic resonance imaging, biomedical optical imaging and fluorescent probes and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591088A_ABST
    Figure CN119591088A_ABST
Patent Text Reader

Abstract

The invention discloses a multifunctional hollow mesoporous degradable carbon nanomaterial as well as a preparation method and application thereof. Monosaccharide is used as a carbon source, core-shell three-dimensional pore structure mesoporous silica is used as a hard template agent, different elements or compounds are embedded into the same carbon nanostructure by adopting a hydrothermal synthesis method based on a non-enzymatic browning reaction, and the carbon nanostructure is prepared. The multifunctional hollow mesoporous degradable carbon nanomaterial with targeting, magnetism, photoluminescence, ultrasonic response, biocompatibility and the like is prepared and has various hollow mesoporous morphologies such as a single-spherical hollow mesoporous shape, a multi-spherical hollow mesoporous shape, a rod-like hollow mesoporous shape, a regular polygonal hollow mesoporous shape and the like, the process is simple, the energy is low, the environment is protected, and the method is suitable for industrial production. The repeatability is good, the particle size ranges from 250 nm to 800 nm, and the monodispersity is good. Therefore, the multifunctional hollow mesoporous degradable carbon nanomaterial has potential application prospects in the fields of catalysis, energy, biomedicine and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material preparation, and specifically relates to a multifunctional hollow mesoporous degradable carbon nanomaterial and a preparation method and application thereof. Background Art

[0002] Hollow mesoporous carbon nanospheres (HMCNs) are widely favored by researchers because of their large specific surface area, low density, loadable cavities, and modifiable internal and external surfaces. However, due to the non-degradable nature of carbon nanomaterials, long-term use will lead to non-negligible cumulative toxicity; in addition, when used in biology, they need to be treated with nitric acid and sulfuric acid for surface functionalization, which causes additional toxicity. Carbon nanomaterials obtained by non-enzymatic browning reactions of sugars have been widely used in the food manufacturing industry. This type of sugar-derived carbon nanomaterial has the characteristics of high biocompatibility, biodegradability and non-toxicity.

[0003] In recent years, with the development of nanotechnology, multifunctional nanomaterials that integrate biomedical imaging diagnosis and treatment, and have the ability to optimize treatment effects and monitor treatment effects have attracted widespread research attention, showing important value and development potential in the diagnosis and treatment of tumors in the medical field. In order to achieve multifunctional integration, most current researchers have combined several materials with different functions by preparing core-shell structures, but the preparation process is often complicated, the materials are unstable, and the results still cannot meet actual needs. Therefore, there is an urgent need for a multifunctional hollow mesoporous carbon nanomaterial that is biodegradable and can be used for diagnosis and treatment. Summary of the invention

[0004] In view of the deficiencies of the prior art, an object of the present invention is to provide a multifunctional hollow mesoporous degradable carbon nanomaterial with good biodegradability.

[0005] Another object of the present invention is to provide a method for preparing a multifunctional hollow mesoporous degradable carbon nanomaterial, which has a simple preparation process, low cost, adjustable particle size and morphology, and good degradability.

[0006] Another object of the present invention is to provide an application of a multifunctional hollow mesoporous degradable carbon nanomaterial, which can be applied to drug delivery, tumor treatment and diagnosis, magnetic resonance imaging, biomedical optical imaging and fluorescent probes.

[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a multifunctional hollow mesoporous degradable carbon nanomaterial, comprising the following steps: (1) adding ammonia water to a mixed solution of deionized water and anhydrous ethanol and stirring the mixture magnetically, then slowly dropping ethyl orthosilicate and continuing to stir the mixture for reaction, and centrifuging, washing and drying the obtained milky white solution to obtain a white powder, which is a solid silica sphere; (2) The white powder obtained in step (1) is dissolved in a mixed solution of deionized water and ethanol, cetyltrimethylammonium bromide (CTAB) is added and stirred at a low speed, tetraethyl orthosilicate (TEOS) and ammonia water are added and stirred overnight, and the obtained mesoporous silica (SiO 2 ) The suspension is centrifuged, dried, and calcined at high temperature in air to selectively remove CTAB in the composite material to obtain a core-shell structured three-dimensional pore structure template material (MSNs); (3) Weighing monosaccharides and the MSNs of step (2) with an electronic balance, adding them to deionized water for ultrasonic dispersion to form a uniform and transparent solution; pouring the solution into a 50 mL high-pressure reactor with a polytetrafluoroethylene liner for high-pressure reaction, centrifuging and washing the product after the reaction to obtain mesoporous carbon nanospheres; placing the mesoporous carbon magnetic nanospheres in a 10%wt hydrofluoric acid solution, stirring, centrifuging, washing until neutral, and drying to obtain a multifunctional hollow mesoporous degradable carbon nanomaterial.

[0008] Furthermore, in step (1), the volume fraction of aqueous ammonia is 25%-30%; the volume ratio of aqueous ammonia, deionized water and anhydrous ethanol is 1-5:1-50:2-100; and the volume ratio of TEOS to aqueous ammonia is 1-4:1-5 (unit: mg / mL).

[0009] Furthermore, in step (1), the temperature of magnetic stirring is 25-30°C; the speed of magnetic stirring is 400-600 rpm; and the stirring reaction time is 1 h.

[0010] Furthermore, in the step (1), the drying temperature is 50°C to 70°C, and the drying time is 5h to 10h.

[0011] Furthermore, in the step (1), the amount of ammonia water used is 1.5-3 mL, and the amount of TEOS used is 1-2 mL.

[0012] Furthermore, in step (2), the mass volume ratio of the white powder to the mixed solution of deionized water and ethanol is 1:1-3; the mass ratio of CTAB to the white powder is 3-6:3-5; the volume ratio of TEOS to ammonia water is 1:1; and the amount of TEOS used is 2-7 times the mass of the white powder (unit: mg / mL).

[0013] Furthermore, in the step (2), the high temperature calcination temperature is 400°C to 1000°C, and the calcination time is 2h to 10h.

[0014] Preferably, in step (2), the high temperature calcination temperature is 500° C. and the calcination time is 5 h.

[0015] Furthermore, the amount of the white powder is 0.03-0.05 g, the amount of the CTAB is 0.03-0.06 g, and the amount of the TEOS is 0.1-0.2 mL.

[0016] Furthermore, in the step (3), the mass ratio of monosaccharide, MSNs and metal salt compound is 2-20:0.7-1:2-20.

[0017] Furthermore, the mass of the monosaccharide is 0.1-1 g, and the mass of the MSNs is 0.035-0.05 g.

[0018] Furthermore, in step (3), the ultrasonic dispersion time is 1 min to 60 min, the ultrasonic power is 40% to 95%, and the operating frequency is 53 KHz.

[0019] Preferably, in step (3), the ultrasonic dispersion time is 30 min, the ultrasonic power is 95%, and the operating frequency is 53 KHz.

[0020] The present invention also provides a multifunctional hollow mesoporous degradable carbon nanomaterial prepared by the preparation method, wherein the particle size is 250 nm to 800 nm, the shell thickness is 20 nm to 50 nm, the cavity size is 100 nm to 200 nm, and the mesopore size is 10 nm to 30 nm.

[0021] Furthermore, the multifunctional hollow mesoporous degradable carbon nanomaterial can be phagocytosed by cells and has good biocompatibility.

[0022] Furthermore, the multifunctional hollow mesoporous degradable carbon nanomaterial is a nano-sized powder.

[0023] Furthermore, the multifunctional hollow mesoporous degradable carbon nanomaterial has magnetic and / or fluorescent properties.

[0024] Furthermore, the degradation time of the multifunctional hollow mesoporous degradable carbon nanomaterial in simulated body fluid (SBF) / simulated lysosomal fluid (SLF) is 30 to 60 days, and the most preferred degradation time is 30 days.

[0025] Furthermore, the degradation time of the multifunctional hollow mesoporous degradable carbon nanomaterial in the tumor cell experiment is 7 to 15 days, and the most preferred degradation time is 7 days.

[0026] The present invention also provides the use of the multifunctional hollow mesoporous degradable carbon nanomaterial in the preparation of delivery drugs, diagnostic reagents or detection reagents.

[0027] The present invention also provides the use of the multifunctional hollow mesoporous degradable carbon nanomaterial in preparing a preparation for magnetic imaging or optical imaging.

[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects: The carbon nanomaterial structure in the present invention belongs to a hollow-mesoporous carbon shell nanomaterial structure. The present invention designs a preparation method, uses monosaccharides as a carbon source, and a core-shell structured three-dimensional pore structured mesoporous silica as a hard template agent. Based on a non-enzymatic browning reaction, a hydrothermal synthesis method is adopted to embed elements or compounds with different properties into the same carbon nanostructure, thereby integrating magnetic response, ultrasonic response, and optical response into a single-phase material, thereby making it possible to realize integrated imaging, diagnosis, and treatment. At the same time, the hollow-mesoporous carbon shell nanomaterial synthesized by the present invention has good biocompatibility, low toxicity, and can be degraded by organisms. Therefore, the carbon nanomaterial of the present invention has potential application value in the fields of catalysis, energy, and biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope (SEM) photograph of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention.

[0030] Figure 2 This is a transmission electron microscope (TEM) photograph of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention.

[0031] Figure 3 This is the TE-1 cell toxicity evaluation of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention.

[0032] Figure 4 This is a toxicological evaluation of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention on mouse organs (heart, liver, spleen, lung, and kidney).

[0033] Figure 5 This is an evaluation of the hemolysis rate of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention in mice.

[0034] Figure 6 This is a Fourier transform infrared (FT-IR) spectrum of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention.

[0035] Figure 7This is an X-ray diffractometer (XRD) analysis of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention.

[0036] Figure 8 This is an X-ray photoelectron spectroscopy (XPS) analysis of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention.

[0037] Fig. 9 Transmission electron microscope (TEM) photos of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention in simulated body fluid (SBF) and simulated lysosomal fluid (SLF) at different times.

[0038] Fig.10 These are transmission electron microscope (TEM) photos of the hollow mesoporous degradable carbon nanomaterial obtained in Example 1 of the present invention in TE-1 cells in vitro at different times.

[0039] Fig.11 This is a transmission electron microscope (TEM) photograph of the hollow mesoporous degradable carbon nanomaterial obtained in Example 4 of the present invention.

[0040] Fig.12 This is a transmission electron microscope (TEM) photograph of the hollow mesoporous degradable carbon nanomaterial obtained in Example 5 of the present invention.

[0041] Fig.13 This is a Fourier transform infrared (FT-IR) spectrum of the hollow mesoporous degradable carbon nanomaterial obtained in Example 12 of the present invention.

[0042] Fig.14 This is the XRD analysis of the hollow mesoporous degradable carbon nanomaterial obtained in Example 12 of the present invention.

[0043] Fig.15 This is the XPS analysis of the hollow mesoporous degradable carbon nanomaterial obtained in Example 12 of the present invention.

[0044] Fig.16 This is a TE-1 cell fluorescence imaging picture of the hollow mesoporous degradable carbon nanomaterial obtained in Example 12 of the present invention. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is further described in detail with reference to the following specific examples.

[0046] In the following examples, unless otherwise specified, the experimental methods used are all conventional methods, and the materials and reagents used can be purchased from biological or chemical reagent companies.

[0047] The test method adopted in the present invention is: 1. Scanning electron microscope (SEM) A SU8010 field emission scanning electron microscope was used to observe the surface morphology, structure and particle size of the samples.

[0048] 2. Transmission electron microscopy (TEM) The surface structure of the samples was analyzed using a HT7700 transmission electron microscope.

[0049] 3. Biocompatibility study (1) In vitro: The cytotoxicity was tested using the CCK-8 method.

[0050] (2) In vivo: Hematoxylin-eosin (HE) staining was used for toxicological analysis.

[0051] (3) Blood compatibility: The hemolysis rate is measured to reflect the hemolysis of the material.

[0052] 4. FT-IR test The analysis was performed using a Nicolet iS20 Fourier transform infrared spectrometer from Thermo Scientific Nicolet, USA.

[0053] 5. Phase structure analysis The Netherlands Panalytical Empyrean X-ray diffraction (XRD) was used to characterize the crystal structure of the samples.

[0054] 6. X-ray Photoelectron Spectroscopy (XPS) The composition and structure of the sample surface were analyzed using X-ray photoelectron spectroscopy (XPS) from Thermo Scientific K-Alpha, USA.

[0055] 7. Fluorescence analysis Fluorescence imaging analysis was performed using an inverted fluorescence microscope from ZEISS, Germany.

[0056] 8. Biodegradability determination (1) Hollow mesoporous biodegradable carbon nanomaterials (HMCNs) were added to simulated fluid (simulated body fluid SBF / simulated lysosomal fluid SLF) at a concentration of 1 mg / mL and shaken in a shaker (150 r / min) at 37°C. Samples were taken out at 5 different time points (1, 5, 10, 20, and 30 days), centrifuged, and washed several times. The precipitate was collected and the morphological changes were observed by TEM.

[0057] (2) TE-1 cells were co-incubated with HMCNs for different time periods (1, 3, and 7 days). At each time point, the cells were collected, fixed, and sliced, and then bio-TEM was used to observe the morphological changes of HMCNs in the cells. Example 1

[0058] In this embodiment, the steps for preparing the hollow mesoporous degradable carbon nanomaterial are as follows: Step S1: Add 2.5 mL of ammonia water (25%) to a mixed solution of 15 mL of deionized water and 30 mL of anhydrous ethanol, and stir magnetically for 5 min at 25-30 °C with a stirring speed of 400-600 rpm; Step S2: Add 2 mL of tetraethyl orthosilicate (TEOS) to the above solution and continue stirring for 1 h to obtain a milky white solution, centrifuge it at 8000 rpm for 5 min, discard the supernatant, and collect the white solid precipitate. Wash it with deionized water and anhydrous ethanol three times each, and dry it at 70°C for 6-8 h to obtain a white powder.

[0059] Step S3: Take 30 mg of the above white powder and dissolve it in 30 mL of a mixed solution of deionized water and ethanol, add 30 mg of hexadecyltrimethylammonium bromide (CTAB) surfactant solution and stir at low speed for 30 min, add 0.2 mL of TEOS and 0.2 mL of ammonia water at 25~30°C and magnetically stir at 400~600 rpm for 12 h to obtain a mesoporous silica suspension.

[0060] Step S4: The obtained mesoporous silica suspension was centrifuged at 8000 rpm / min for 10 min and then dried at 70°C. The obtained mesoporous silica was calcined at 500°C in a muffle furnace for 5 h to selectively remove CTAB in the composite material, and finally a core-shell structured three-dimensional pore structure template material (MSNs) was obtained.

[0061] Step S5: Use an electronic balance to weigh 0.5 g monosaccharide and 0.035 g core-shell three-dimensional mesoporous silica (MSNs), and add them to 35 mL of H 2 O for 30 min with ultrasonic power of 95% and working frequency of 53KHz to form a uniform and transparent solution.

[0062] Step S6: Pour the mixed solution into a 50 mL high-pressure reactor with a polytetrafluoroethylene liner and react at 180° C. for 5 h. After the reaction is completed, take out the product from the reactor, and obtain mesoporous carbon nanospheres with MSNs as the core by conventional centrifugation and washing.

[0063] Step S7: The mesoporous carbon nanospheres with the MSNs as the core are placed in a hydrofluoric acid solution, stirred, centrifuged, washed until neutral, and then dried in an oven at 70° C. for 7-8 h to obtain degradable hollow mesoporous carbon spheres (HMCNs).

[0064] The SEM and TEM results of this example show that the obtained material has a unique hollow single spherical mesoporous structure with uniform morphology and a particle size of about 250 nm. Figure 1 and Figure 2 The cell activity was above 85%, the hemolysis rate was less than 5%, there was no obvious pathological damage, and the biocompatibility was good. Figure 3 , Figure 4 and Figure 5 FT-IR analysis shows that the presence of a large number of hydroxyl groups in the product HMCNs after the hydrothermal reaction can improve the hydrophilicity and stability of HMCNs in aqueous systems, see Figure 6 XRD results show that HMCNs exist in an amorphous carbon structure, see Figure 7 XPS identified two characteristic absorption peaks related to C1s (284~288 eV) and O1s (532~534 eV), see Figure 8 The degradation time in simulated fluid (SBF / SLF) is 30 days, see Fig. 9 The degradation time in in vitro cells is 7 days, see Fig.10 . Example 2

[0065] The implementation process is the same as Example 1 except for the following differences.

[0066] Step S5: Use an electronic balance to weigh 1 g of monosaccharide and 0.035 g of core-shell three-dimensional mesoporous silica (MSNs), and add them to 35 mL of H 2 O for 30 min with ultrasonic power of 95% and working frequency of 53KHz to form a uniform and transparent solution.

[0067] The results obtained are basically similar to those in Example 1. In this embodiment, the SEM and TEM results show that the obtained degradable hollow mesoporous carbon nanomaterial is a complete hollow single spherical mesoporous carbon sphere structure with uniform morphology and a particle size of about 310 nm. The cell activity is above 85%, the hemolysis rate is <5%, there is no obvious pathological damage, and the biocompatibility is good. FT-IR analysis shows that the presence of a large number of hydroxyl groups in the product CHMCNs after the hydrothermal reaction can improve the hydrophilicity and stability of CHMCNs in an aqueous system. XRD results show that CHMCNs exist in an amorphous carbon structure. XPS identifies two characteristic absorption peaks related to C1s (284~288 eV) and O1s (532~534 eV). The degradation time in the simulated liquid (SBF / SLF) is 30 days. The degradation time in in vitro cells is 7 days. Example 3

[0068] The implementation process is the same as Example 1 except for the following differences.

[0069] Step S5: Use an electronic balance to weigh 0.1 g monosaccharide and 0.035 g core-shell three-dimensional mesoporous silica (MSNs) and add them to 35 mL of H 2 O for 30 min with ultrasonic power of 95% and working frequency of 53KHz to form a uniform and transparent solution.

[0070] Step S6: Pour the above mixed solution into a 50 mL high-pressure reactor with a polytetrafluoroethylene liner and react at 180° C. for 8 h. After the reaction is completed, take the product out of the reactor and undergo conventional centrifugation, washing and other steps.

[0071] The obtained results are completely different from those in Example 1. No degradable hollow mesoporous carbon nanomaterials were obtained in this example. Example 4

[0072] The implementation process is the same as Example 1 except for the following differences.

[0073] Step S5: Use an electronic balance to weigh 0.5 g monosaccharide, 0.035 g core-shell three-dimensional pore structure mesoporous silica (MSNs) and 0.05 g, and add them to 35 mL of H 2 O was properly dispersed by ultrasound for 5 min; the ultrasonic power was 65% and the operating frequency was 53KHz.

[0074] The SEM and TEM results in this example show that the obtained degradable hollow mesoporous carbon nanomaterial is a complete hollow double sphere structure with a particle size of 350-500 nm. Fig.11 . The cell activity was above 85%, the hemolysis rate was <5%, there was no obvious pathological damage, and the biocompatibility was good. FT-IR analysis showed the presence of a large number of hydroxyl groups in the product CHMCNs after the hydrothermal reaction, which could improve the hydrophilicity and stability of CHMCNs in aqueous systems. XRD results showed that CHMCNs existed in an amorphous carbon structure. XPS identified two characteristic absorption peaks related to C1s (284~288 eV) and O1s (532~534 eV). The degradation time in simulated fluid (SBF / SLF) was 35 days. The degradation time in in vitro cells was 9 days. Example 5

[0075] The implementation process is the same as Example 1 except for the following differences.

[0076] Step S5: Use an electronic balance to weigh 0.5 g monosaccharide and 0.035 g core-shell three-dimensional mesoporous silica (MSNs), and add them to 35 mL of H 2 O for 1 min to properly disperse; the ultrasonic power was 40%.

[0077] The SEM and TEM results in this example show that the obtained degradable hollow mesoporous carbon nanomaterial is a complete hollow multi-sphere structure with a particle size of 500-700 nm. Fig.12 . The cell activity was above 85%, the hemolysis rate was <5%, there was no obvious pathological damage, and the biocompatibility was good. FT-IR analysis showed that a large number of hydroxyl groups were present in the product CHMCNs after the hydrothermal reaction, which could improve the hydrophilicity and stability of CHMCNs in aqueous systems. XRD results showed that CHMCNs existed in an amorphous carbon structure. XPS identified two characteristic absorption peaks related to C1s (284~288 eV) and O1s (532~534 eV). The degradation time in simulated fluid (SBF / SLF) was 45 days. The degradation time in in vitro cells was 15 days. Example 6

[0078] The implementation process is the same as Example 1 except for the following differences.

[0079] Step S5: Use an electronic balance to weigh 0.1 g monosaccharide and 0.035 g core-shell three-dimensional mesoporous silica (MSNs) and add them to 35 mL of H 2 O for 30 min with ultrasonic dispersion at 95% ultrasonic power and 53KHz working frequency to form a uniform and transparent solution; The obtained results are completely different from those in Example 1. No degradable hollow mesoporous carbon nanomaterials were obtained in this example. Example 7

[0080] The implementation process is the same as Example 1 except for the following differences.

[0081] Step S5: Use an electronic balance to weigh 0.5 g monosaccharide and 0.035 g core-shell three-dimensional mesoporous silica (MSNs), and add them to 35 mL of H 2 O for 30 min with ultrasonic power of 95% and working frequency of 53KHz to form a uniform and transparent solution.

[0082] Step S6: Pour the mixed solution into a 50 mL high-pressure reactor with a polytetrafluoroethylene liner and react at 180°C for 8 hours. After the reaction is completed, take out the product from the reactor and obtain mesoporous carbon nanospheres with MSNs as the core through conventional centrifugation, washing and other steps.

[0083] The results obtained are basically similar to those in Example 1. The SEM and TEM results in this example show that the obtained degradable hollow mesoporous carbon nanomaterial is a complete hollow single spherical mesoporous carbon sphere structure, with a particle size of about 270 nm, cell activity of more than 85%, hemolysis rate <5%, no obvious pathological damage, and good biocompatibility. FT-IR analysis shows that the presence of a large number of hydroxyl groups in the product HMCNs after the hydrothermal reaction can improve the hydrophilicity and stability of CHMCNs in an aqueous system. XRD results show that CHMCNs exist in an amorphous carbon structure. XPS identifies two characteristic absorption peaks related to C1s (284~288 eV) and O1s (532~534 eV). The degradation time in the simulated liquid (SBF / SLF) is 30 days. The degradation time in in vitro cells is 7 days. Example 8

[0084] The implementation process is the same as Example 1 except for the following differences.

[0085] Step S5: Use an electronic balance to weigh 1 g of monosaccharide and 0.035 g of core-shell three-dimensional mesoporous silica (MSNs), and add them to 35 mL of H 2 O for 30 min with ultrasonic power of 95% and working frequency of 53KHz to form a uniform and transparent solution.

[0086] Step S6: Pour the mixed solution into a 50 mL high-pressure reactor with a polytetrafluoroethylene liner and react at 180°C for 8 hours. After the reaction is completed, take out the product from the reactor and obtain mesoporous carbon nanospheres with MSNs as the core through conventional centrifugation, washing and other steps.

[0087] The results obtained are basically similar to those in Example 1. The SEM and TEM results in this example show that the obtained degradable hollow mesoporous carbon nanomaterial is a complete hollow single spherical mesoporous carbon sphere structure, with a particle size of about 330 nm, cell activity of more than 85%, hemolysis rate <5%, no obvious pathological damage, and good biocompatibility. FT-IR analysis shows that the presence of a large number of hydroxyl groups in the product CHMCNs after the hydrothermal reaction can improve the hydrophilicity and stability of CHMCNs in an aqueous system. XRD results show that CHMCNs exist in an amorphous carbon structure. XPS identifies two characteristic absorption peaks associated with C1s (284~288 eV) and O1s (532~534 eV). The degradation time in the simulated liquid (SBF / SLF) is 35 days. The degradation time in in vitro cells is 9 days. Example 9

[0088] The implementation process is the same as Example 1 except for the following differences.

[0089] Step S5: Use an electronic balance to weigh 0.5 g monosaccharide and 0.035 g core-shell three-dimensional mesoporous silica (MSNs), and add them to 35 mL of H 2 O for 30 min with ultrasonic power of 95% and working frequency of 53KHz to form a uniform and transparent solution.

[0090] Step S6: Pour the mixed solution into a 50 mL high-pressure reactor with a polytetrafluoroethylene liner and react at 180° C. for 2 h. After the reaction is completed, take the product out of the reactor and undergo conventional centrifugation, washing and other steps.

[0091] The obtained results are completely different from those in Example 1. No degradable hollow mesoporous carbon nanomaterials were obtained in this example. Example 10

[0092] The implementation process is the same as Example 1 except for the following differences.

[0093] Step S5: Use an electronic balance to weigh 0.5 g monosaccharide and 0.035 g core-shell three-dimensional mesoporous silica (MSNs), and add them to 35 mL of H 2 O for 30 min with ultrasonic power of 95% and working frequency of 53KHz to form a uniform and transparent solution.

[0094] Step S6: Pour the mixed solution into a 50 mL high-pressure reactor with a polytetrafluoroethylene liner and react at 160° C. for 5 h. After the reaction is completed, take the product out of the reactor and undergo conventional centrifugation, washing and other steps.

[0095] The obtained results are completely different from those in Example 1. No degradable hollow mesoporous carbon nanomaterials were obtained in this example. Embodiment 11

[0096] The implementation process is the same as Example 1 except for the following differences.

[0097] Step S5: Use an electronic balance to weigh 0.5 g monosaccharide and 0.035 g core-shell three-dimensional mesoporous silica (MSNs), and add them to 35 mL of H 2 O for 30 min with ultrasonic power of 95% and working frequency of 53KHz to form a uniform and transparent solution.

[0098] Step S6: Pour the mixed solution into a 50 mL high-pressure reactor with a polytetrafluoroethylene liner and react at 140°C for 8 hours. After the reaction is completed, take out the product from the reactor and obtain mesoporous carbon nanospheres with MSNs as the core through conventional centrifugation, washing and other steps.

[0099] The obtained results are completely different from those in Example 1. No degradable hollow mesoporous carbon nanomaterials were obtained in this example. Example 12

[0100] The implementation process is the same as Example 1 except for the following differences.

[0101] Step S5: 0.5 g monosaccharide, 0.035 g core-shell three-dimensional mesoporous silica (MSNs), and 0.05 g manganese chloride tetrahydrate and / or fluorescent dye were weighed using an electronic balance and added to 35 mL of H 2 O for 30 min with ultrasonic power of 95% and working frequency of 53KHz to form a uniform and transparent solution.

[0102] The obtained material is basically similar to that of Example 1. The SEM and TEM results show that the obtained hollow mesoporous carbon nanomaterial is a complete hollow single spherical mesoporous carbon sphere structure with uniform morphology, a particle size of about 310 nm, magnetic and / or fluorescent, cell activity of more than 85%, hemolysis rate <5%, no obvious pathological damage, and good biocompatibility. FT-IR analysis shows that the presence of a large number of hydroxyl groups in the product CHMCNs after the hydrothermal reaction can improve the hydrophilicity and stability of CHMCNs in aqueous systems, see Fig.13 XRD results show that CHMCNs exist in an amorphous carbon structure, see Fig.14 XPS identified three characteristic absorption peaks related to C1s (284~291 eV), O1s (532~535 eV) and Mn 2p (640~656 eV), see Fig.15 . Fluorescence microscope images show that it can be used for fluorescence imaging analysis, see Fig.16 The degradation time in simulated fluid (SBF / SLF) was 30 days. The degradation time in in vitro cells was 7 days.

[0103] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.

Claims

1. A method for preparing a multifunctional hollow mesoporous degradable carbon nanomaterial, characterized in that: The following steps are involved: (1) adding ammonia water to a mixed solution of deionized water and anhydrous ethanol and stirring, then dropping ethyl orthosilicate and continuing to stir the reaction, and obtaining a milky white solution through centrifugation, washing and drying to obtain a white powder, wherein the white powder is a solid silica sphere; (2) dissolving the white powder obtained in step (1) in a mixed solution of deionized water and ethanol, adding hexadecyltrimethylammonium bromide, ethyl orthosilicate and ammonia water, stirring, and centrifuging, drying and calcining the obtained mesoporous silica suspension to obtain a core-shell structured three-dimensional pore structure template material; (3) Weighing monosaccharides and the three-dimensional pore structure template material of step (2), adding them into water and ultrasonically dispersing them to form a uniform and transparent solution; The solution is subjected to high pressure reaction, and the product after the reaction is centrifuged and washed to obtain mesoporous carbon nanospheres; The mesoporous carbon nanospheres are placed in a hydrofluoric acid solution, stirred, centrifuged, washed until neutral, and then dried to obtain a multifunctional hollow mesoporous degradable carbon nanomaterial.

2. The preparation method according to claim 1, characterized in that: In the step (1), the volume fraction of ammonia water is 25%-30%; the volume ratio of ammonia water, deionized water and anhydrous ethanol is 1-5:1-50:2-100; and the volume ratio of tetraethyl orthosilicate to ammonia water is 1-4:1-5.

3. The preparation method according to claim 1, characterized in that: In the step (1), the drying temperature is 50°C to 70°C, and the drying time is 5h to 10h.

4. The preparation method according to claim 1, characterized in that: In the step (2), the mass volume ratio of the white powder to the mixed solution of deionized water and ethanol is 1:1-3; the mass ratio of hexadecyltrimethylammonium bromide to the white powder is 3-6:3-5; the volume ratio of tetraethyl orthosilicate to ammonia water is 1:1; and the amount of tetraethyl orthosilicate used is 2-7 times the mass of the white powder.

5. The preparation method according to claim 1, characterized in that: In the step (2), the high temperature calcination temperature is 400°C to 1000°C, and the calcination time is 2h to 10h.

6. The preparation method according to claim 1, characterized in that: In the step (3), the mass ratio of monosaccharide, three-dimensional pore structure template material, and metal salt compound is 2-20:0.7-1:2-20.

7. The preparation method according to claim 1, characterized in that: In the step (3), the ultrasonic dispersion time is 1 min to 60 min, the ultrasonic power is 40% to 95%, and the operating frequency is 53 KHz.

8. The multifunctional hollow mesoporous degradable carbon nanomaterial prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The multifunctional hollow mesoporous degradable carbon nanomaterial has a particle size of 250 nm to 800 nm, a shell thickness of 20 nm to 50 nm, a cavity size of 100 nm to 200 nm, and a mesopore size of 10 nm to 30 nm.

9. Use of the multifunctional hollow mesoporous degradable carbon nanomaterial according to claim 8 in the preparation of delivery drugs, diagnostic agents or detection agents.

10. Use of the multifunctional hollow mesoporous degradable carbon nanomaterial according to claim 8 in preparing a preparation for magnetic imaging or optical imaging.